Ζυμούμενο ρόφημα από γαϊδουρινό γάλα: μικροβιολογικά, χημικά, οργανοληπτικά χαρακτηριστικά και λειτουργικότητα - Παρμαξή, Ιωάννα (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
This study investigated the possibility of producing two new probiotic fermented beverages from donkey’s milk using the probiotic strains Lactobacillus fermentum ME- 3 and Lactobacillus acidophilus (ATCC 4356). The microbiological and chemical properties of ass's milk showed that it contains a low microbiological load (104 cfu/ml), a low protein (0.8 %) and fat (0.5 %) content and an elevated content of lysozyme (60372 U/ml). For the creation of the fermented beverages, the pasteurized ass's milk was inoculated with 5% inoculum of the two cultures respectively and incubated at 37°C until the pH fall approximately to 4.6. The bacterial strains used for fermentation had a good growth capacity in ass’s milk. Upon completion of the fermentation, the products contained lactic acid bacteria of about 108-109 cfu/ml, with 0.31 to 0.35% titratable acidity and pH 4.6. During storage in the refrigerator both strains showed good survival and the number of viable microorganisms remain substantially stable during 14 days of storage. Similarly, the activity of lysozyme was almost unchanged compared with the initial values and was not affected by heat treatment (63οC for 30 minutes). Through the study of antimicrobial and antioxidant activity of fermented beverages, the latter characterized by a relatively high total antioxidant capacity and a significant antimicrobial activity against specific strains of pathogens (Salmonella and E. coli). The above functional properties probably related to the increased proteolytic ability of both probiotic strains. Moreover, the sensory analysis allowed the identification of differences between the two bacterial strains used for the fermentation for characteristics which were associated with the aromatic, olfactory and gustatory properties. These findings will allow the production of two new probiotic fermented beverages made from a non-cow's milk characterized by properties which will promote health and be accepted by people who are allergic to cow's milk.
Keywords: Donkey’s Milk; Lactobacillus Fermentum; Lactobacillus Acidophilus; Γάλα Γαϊδούρας